MENGENALILEBIH DEKAT PATROLOGI - Antonius Eddy Kristiyanto (P3TK, Sanata Dharma University, 2013)
Writings of the Fathers of the Church and their theological vision have made great impact on the Churchs teaching and its theology. Mostly their work are related to Scripture, liturgy and life of the Church, responding to questions and concerns of their time as well as reflecting philosophical teachings of their time. On the other hand, their approach and method, message and its significance go beyond their time and place of origin as well as pointing to new visions that can be continuously studied, to serve as a guide for todays Church. We will discuss some basic criteria on how one is considered Father of the Church, with his historical mission. On the other hand, we shall learn some common characteristics of the Patristic theology. This article is an attempt to explicate those fundamental characteristics while indicating some important points to develop a contextual theology and a theology in response to the questions of our own time.